Preparation a New SHE-Medium Replacement of RPMI1640-Medium using Oral Rehydration Solution - Ekhlass N. Ali (Journal of Global Pharma Technology, 2020)
The study showed that the use of the new culture medium which called (SHE-medium) prepared by using oral rehydration salts, led to increase the ratio of cell viability of PMNs and lymphocytes compare with RPMI 1640-medium on 24,48,72 h. The results shows that ratio of cell viability of PMNs in SHE-medium were 89%,91% ,93% respectively, while in RPMI 1640-medium were 80%,90%,93% respectively while the ratio of cell viability of lymphocyte in SHE-medium were 88%,90% ,91% respectively, compare with RPMI 1640-medium which are 80%,85%,90% respectively. But when tested the effect of SHE-medium on THP-1 cell line and REF cells and comparison with RPMI 1640-medium, the results shows that the ratio of cell viability on SHE-medium were 84.33% and 74.33% respectively, while in RPMI 1640-medium were 86.67% and 80.67% respectively.Keywords: 1640-medium, SHE-medium, Oral rehydration solution.